Rights Based Management and the Reform of the Common fisheries Policy: An Evaluation of Portuguese Experience - Coelho, Manuel (2010)
Recently, the Pew Environment Group released a study that finds that E. U. fisheries have failed to reduce fleet capacity thus exerting fishing pressure on stocks at two/three time sustainable levels. The members evaluated in this study accounted for more than 90% of European fisheries subsidies. Overcapacity and overcapitalisation of the sector was identified as the principal failure of the Common Fisheries Policy. The study also highlights that member-states failed to take environmental and social concerns into consideration when allocating public funding. This conclusion may be well important in the CFP reform (2012) and put again the discussion about the tools that can be used to get sustainable management and better cohesion. The idea of creating markets for fishing rights as a means of internalising the externalities derived from the common property nature of fisheries have received considerable attention by the founding fathers of Law and Economics and Fisheries Economics such as Coase, Scott and Christy. The idea is to create a market of individual transferable quotas (ITQs) and confide in the self-regulation of such a system to conduct the fisheries to the economic efficiency and to promote inter¬temporal sustainable use of resources. Rights Based Management schemes have already been experimented in some specific fisheries and localizations. These experiences have a lot of teaching results about good practices of sustainable fisheries management and also about the limitations/ risks of these tools. These conclusions are fundamental to explore the feasibility of these tools as instruments of conservation in the CFP. The purpose of our Communication is to enter this debate and evaluate the Portuguese experience with rights based management.